2017
DOI: 10.1242/dev.145235
|View full text |Cite
|
Sign up to set email alerts
|

IP3R mediated Ca2+ release regulates protein metabolism inDrosophilaneuroendocrine cells: implications for development under nutrient stress

Abstract: Successful completion of animal development is fundamentally reliant on nutritional cues. Surviving periods of nutritional insufficiency requires adaptations that are coordinated, in part, by neural circuits. As neuropeptides secreted by neuroendocrine (NE) cells modulate neural circuits, we investigated NE cell function during development under nutrient stress. Starved Drosophila larvae exhibited reduced pupariation if either insulin signaling or IP3/Ca2+ signaling were downregulated in NE cells. Moreover, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The ability to pupariate on nutrient-restricted (NR) media (100mM sucrose) as opposed to a complex mixture of yeast, sugar and corn flour ("normal" food), when transferred in the last stage of larval development (~88 hours post egg laying), was used as a measure of development. Collectively, more than 20 different NPs are made by the NE cells in which reducing SOCE components resulted in poor pupariation upon NR (11). From these NPs, those with established roles in feeding and metabolism were selected and, a curated GAL4-UAS genetic screen undertaken.…”
Section: Soce Is Required In Crz and Snpf Producing Neurons For Develmentioning
confidence: 99%
See 3 more Smart Citations
“…The ability to pupariate on nutrient-restricted (NR) media (100mM sucrose) as opposed to a complex mixture of yeast, sugar and corn flour ("normal" food), when transferred in the last stage of larval development (~88 hours post egg laying), was used as a measure of development. Collectively, more than 20 different NPs are made by the NE cells in which reducing SOCE components resulted in poor pupariation upon NR (11). From these NPs, those with established roles in feeding and metabolism were selected and, a curated GAL4-UAS genetic screen undertaken.…”
Section: Soce Is Required In Crz and Snpf Producing Neurons For Develmentioning
confidence: 99%
“…Flies were grown at 25 o C in 12h:12h L:D cycle. Recipe for normal food (11). For nutritional stress assay, flies were allowed to lay eggs for 6 hours on normal food.…”
Section: Fly Husbandrymentioning
confidence: 99%
See 2 more Smart Citations
“…dependant enzymes such as CamKII, previous reports have shown that knock-down of the IP 3 R in Drosophila larval neurons alters their expression profile and specifically affects the expression of several membrane localised ion-channels (Jayakumar et al, 2018). Reduced translation of proteins due to IP 3 R knockdown has also been demonstrated in peptidergic neurons (Megha & Hasan, 2017). Changes in membrane excitability could thus derive from direct regulation of ion channels by Ca 2+ and Ca 2+ dependant enzymes as well as an altered density of specific ion channels.…”
Section: Intracellular Ca 2+ Signaling and Neuronal Excitabilitymentioning
confidence: 97%